Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Wei, Maochun; Chen, Keyu; Lin, Yating; Cheng, En (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out many researches on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish, but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure which is level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of Penaeus vannamei are collected based on passive acoustic technology, and their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic Non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of Penaeus vannamei, to achieve the purpose of real-time monitoring of the behavior state of Penaeus vannamei. The experimental results show that LPCC and MFCC characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of Penaeus vannamei. Meanwhile the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently, and has a classification accuracy as high as 93%.